THE IMPACT OF THE MIGRATION CRISIS AND POSSIBLE SOLUTIONS IN THE CONTEXT OF LIFELONG LEARNING - Jurs, Pāvels; Neimane, Ilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In 2015, Europe experienced a migrant crisis – The European Union has faced an unprecedented influx of refugees and migrants. More than one million people arrived in the European Union, most fleeing war and terror in Syria and other countries, for example, the number of immigrants crossing the sea from Turkey to Greece per day (October 20, 2015) was 1,0006 people, as shown by the data of European Commission (European Commission, 2017). The migrant crisis in Europe and its consequences are our collective responsibility as Europeans and the ability to show solidarity by providing immigrants with much needed support, based on generally accepted human rights and moral responsibility issues. Along with the challenges posed by the migrant crisis the issue came up of better integration of immigrants into society, providing the necessary information regarding the assistance offered, providing the necessary information regarding the assistance offered social guarantees, protection, and knowledge of local culture, traditions, history and educational opportunities. The aim of the article is to share good practices in the field of lifelong learning by implementing an international pilot project aimed at training migrants in the context of lifelong learning, based on theoretical research methods on the consequences and challenges of the migrant crisis, as well as based on empirical research (statistical analysis, analysis of survey results, development of interactive learning environment). The main findings of the authors of the study are reflected in the interactive learning platform created within the framework of the international project, as well as the authors' recommendations for non – formal education of migrants in the context of lifelong learning.